PENGARUH KUALITAS PELAYANAN RUMAH MAKAN BRUNAI TERHADAP KEPUASAN PELANGGAN DI KELURAHAN SERASAN JAYA SEKAYU - Ade Nia Suryani (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2019)
The purpose of this study was to determine the effect of the service quality of the Brunai Restaurant on customer satisfaction in Serasan Jaya Sekayu Village. This research is an associative causality research. The population of this study is all customers of Brunai restaurants. The total sample of 100 people were determined using the Malhotra formula. Data were analyzed using simple linear regression analysis and correlation analysis. The results showed that the correlation value (R) of 0,762 means that there was a strong relationship between the quality of service in the Brunai Restaurant and customer satisfaction. While the coefficient of determination (R ) of 0,646 means that 64,6% of customer satisfaction (Y) is influenced by the quality of the Brunai Restaurant service (X), the remaining 35,4% is caused by other factors.